2017
DOI: 10.3390/su9122171
|View full text |Cite
|
Sign up to set email alerts
|

Measure the Performance with the Market Value Added: Evidence from CSR Companies

Abstract: An increasing number of firms in OECD countries are obtaining certification as Socially Responsible. Literature is sensitive in testing whether there is a relation between firm performance and Social Responsibility certification. In order to overcome problems related to the multiplicity of Corporate Social Responsibility (CSR) definitions and certifications, our work implements a CSR index based on the intersection between two of the three main international indices (Domini 400 Social Index, Dow Jones Sustaina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 116 publications
(156 reference statements)
1
24
0
2
Order By: Relevance
“…They found that there is a significant negative short-term impact of CSR adoption and business performance. The CSR-CFP Corporate Financial Performance (CFP) relationship was visited again by several authors (Škare & Golja, 2012;Pätäri, Arminen, Tuppura, & Jantunen, 2014;Vergini, Jacomossi, Turra, & Hein, 2015;Rodriguez-Fernandez, 2016;Carini, Comincioli, Poddi, & Vergalli, 2017;Choongo, 2017;Oh, Hong, & Hwang, 2017;Ang & Weber, 2018;Beck, Frost, & Jones, 2018;Hategan, Sirghi, Curea-Pitorac, & Hategan, 2018;Cherian et al, 2019;Lin, Hung, et al, 2019;Lin, Law, et al, 2019), some of which considered environmental leadership (DiSegni, Huly, & Akron, 2015), its impact on innovation, and firm performance as possible moderating variables (Martinez-Conesa, Soto-Acosta, & Palacios-Manzano, 2017). Ekatah, Samy, Bampton, and Halabi (2011) sought to explore whether CSR is linked to profitability employing simple statistic methods and linear regression.…”
Section: Overview Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…They found that there is a significant negative short-term impact of CSR adoption and business performance. The CSR-CFP Corporate Financial Performance (CFP) relationship was visited again by several authors (Škare & Golja, 2012;Pätäri, Arminen, Tuppura, & Jantunen, 2014;Vergini, Jacomossi, Turra, & Hein, 2015;Rodriguez-Fernandez, 2016;Carini, Comincioli, Poddi, & Vergalli, 2017;Choongo, 2017;Oh, Hong, & Hwang, 2017;Ang & Weber, 2018;Beck, Frost, & Jones, 2018;Hategan, Sirghi, Curea-Pitorac, & Hategan, 2018;Cherian et al, 2019;Lin, Hung, et al, 2019;Lin, Law, et al, 2019), some of which considered environmental leadership (DiSegni, Huly, & Akron, 2015), its impact on innovation, and firm performance as possible moderating variables (Martinez-Conesa, Soto-Acosta, & Palacios-Manzano, 2017). Ekatah, Samy, Bampton, and Halabi (2011) sought to explore whether CSR is linked to profitability employing simple statistic methods and linear regression.…”
Section: Overview Of the Literaturementioning
confidence: 99%
“…The most commonly employed market valuation variables for financial performance were 5-year cumulative share increase (DiSegni et al, 2015), capital asset pricing model (Carini et al, 2017), and value in trading day compared to value on previous trading day (Ang & Weber, 2018).…”
Section: Trends For Future Researchmentioning
confidence: 99%
“…Many empirical studies on the relationship between CSR and firm value report inconsistent results. Some studies report a positive relationship between CSR performance and firm value [2][3][4][5][6][7][8][9], while others find a negative [10][11][12][13] or irrelevant relationship [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are still contradicting ideas on the signs of the relationship between CSR and financial performance. The documented sign of the relationship may indicate negative [3], neutral [4], or positive [5][6][7][8] linkages. Accounting and finance researchers have also documented important findings on the benefits of CSR, such as reduced business risk, information asymmetry, cost of capital, insider trading profit and analyst forecast errors and increased customer trust and loyalty, employee retention, productivity, and company reputation.…”
Section: Introductionmentioning
confidence: 99%